Food and cash transfers coupled with nutrition behavior change communication lead to sustained reductions in intimate partner violence in Bangladesh - Cash Transfer and Intimate Partner Violence Research Collaborative (International Food Policy Research Institute, 2019)
This case study from Bangladesh summarizes findings from a transfer program that—when paired with nutrition behavior change communication (BCC)—led to a 26 percent reduction in physical IPV that was sustained after the program ended. Pathways of impact include increases in women’s bargaining power, social interactions, and visibility, and decreases in poverty and poverty-related stress.